EVALUASI IMPLEMENTASI PENGGUNAAN IT (Information Technology) OLEH GURU DALAM SISTEM BELAJAR DARI RUMAH - Iin Siti Sutarsih Sadikin; Nini Aryani; Nopa Wilyanita (P3M STKIP 'Aisyiyah Riau, 2021)
Abstract: the study aims to know how to analyze and describe the results of application of it (information technology) by the teacher in BDR. In doing this study, researchers use a qualitative method of study with a descriptive approach to get information on the implementation of the use of it (information technology) by the teacher in BDR. The data analysis technique in this study is to reproduce the data. By reducing this data, researchers are looking for truly valid data and reject nonessential data in the data presentation.. Implementation evaluations of the use of it (information technology) by the teacher in BDR on context (contexs) have filled the context aspect according to the modelp model, with input (input) well, while the process (process) is done well and what is done by product (product) is done well. This condition means that the use of it by the teacher in BDR is working properly